The Caenorhabditis elegans Proteome Response to Naturally Associated Microbiome Members of the Genus Ochrobactrum. Issue 8 (30th March 2018) - Cassidy, Liam; Petersen, Carola; Treitz, Christian; Dierking, Katja; Schulenburg, Hinrich; Leippe, Matthias; Tholey, Andreas
Abstract: The nematode Caenorhabditis elegans interacts with a variety of bacteria as it feeds on microbes, and a number of these both associate and persist within the worm's intestine. Host–microbe interactions in C. elegans have been analyzed primarily at the transcriptome level with the host response often been monitored after challenge with pathogens. We assessed the proteome of C. elegans after growth on bacteria capable of colonizing its gut, via a comparative analysis of the nematode exposed to two naturally associated Ochrobactrum spp. (MYb71, MYb237) versus C. elegans grown on Escherichia coli OP50. A total of 4677 C. elegans proteins were identified, 3941 quantified. Significant alterations in protein abundances were observed for 122 proteins, 48 higher and 74 lower in abundance. We observed an increase in abundance of proteins potentially regulated via host signaling pathways, in addition to proteins involved in processing of foreign entities (e.g., lipase, proteases, glutathione metabolism). Decreased in abundance were proteins involved in both degradation and biosynthesis of amino acids, and enzymes associated with the degradation of peptidoglycan (lysozymes). The protein level differences between C. elegans grown on native microbiome members compared to the laboratory food bacterium may help to identify molecular processes involved in host–microbe interactions.